ETNOBOTANI TUMBUHAN OBAT DI DESA BARENE KECAMATAN MALAKA TENGAH KABUPATEN MALAKA - Josyandy Vony Demira Kause; Theodora S.N Manu; Yanti Daud (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2020)
ABSTRACTResearch is a ethnobotany of medicinal plants in Barene Village, Central Malaka District, Malacca Regency which aims to find out what types of plants are utilized by the people of Barene Village, what plant organs are used in medicine, how to process these plants for traditional medicine and the benefits of medicinal plants. Sampling was conducted in Barene Village, Central Malaka District, Malacca District. This type of research is a descriptive study with a sampling technique approach conducted by purposive sampling. Data collection methods used are observation, interviews, and documentation. Data from the results of subsequent studies were analyzed descriptively qualitatively according to the purpose of the study which would later be presented in the form of tables, photographs or images. The results showed that in Barene Village there were 20 types of plants that were used by the community as traditional medicine. Plant organ parts used in medicine are leaves, leaf buds, roots, bark, rhizomes, leaves and bark. How to process these plants in traditional medicine that is boiled, chewed, eaten, pounded, and soaked. The people of Barene Village use the ingredients more often by boiling and then drinking. The part that is most used by the people of Barene Village as a treatment for the use of leaves. The benefits of traditional medicinal plants are efficacious in curing several types of diseases.Keywords: Ethnobotany, Medicinal Plants, Barene Village Community